Controlled/living surface-initiated ATRP of antifouling polymer brushes from gold in PBS and blood sera as a model study for polymer modifications in complex biological media - Rodriguez-Emmenegger, Cesar; Hasan, Erol; Pop-Georgievski, Ognen; Houska, Milan; Brynda, Eduard; Alles, Aldo Bologna (Macromolecular bioscience, 2012)
The use of PBS, 10% FBS or 10% CS as media for SI-ATRP is reported. Controlled/living SI-ATRP of MeOEGMA in PBS is achieved leading to better control than in water. The livingness is confirmed by chain extension with MeOEGMA or carboxybetaine acrylamide. This technique is successfully adopted for the polymerization of MeOEGMA in 10% FBS or CS as models for complex biological media with reasonable control of the brush growth. All prepared brushes show excellent antifouling properties.
Keywords: Adsorption; adsorpce; voda; akrylamidy; Water; Biocompatible Materials; Materials Testing; krevní proteiny; Methacrylates; Animals; Buffers; Acrylamides; Serum; zvířata; testování materiálů; Cattle; Gold; skot; sérum; zlato; Blood Proteins; spektroskopie infračervená s Fourierovou transformací; methakryláty; pufry; polyethylenglykoly; Polymerization; Spectroscopy, Fourier Transform Infrared; biokompatibilní materiály; Polyethylene Glycols; polymerizace